The Howz-e Shamsi and the Making of an Islamic Sacred Site in the Urban Space of Delhi - Ninomiya, Ayako (Journal of Persianate studies, 2023)
Sacred sites are loci with a special relationship with a particular religion and are indicators of religious indigenization. The Howz-e Shamsi (“Reservoir of Shams”) is one such structure considered sacred during the Delhi Sultanate period. Built around 1230 by Shams al-Din Eltotmesh b. Elam Khān (r. 1211–36), the reservoir served as an important element of urban infrastructure. The process of its sacralization can be traced in various Persian sources, mostly discourses (malfuzāt) of famous Cheshti Sufi masters. Although some works consulted in this study, such as Favāʾed al-sālekin (Benefits of the Seekers) and Meftāh al-tālebin (The Key of the Seekers), are considered fabricated and have been ignored in prior research, these texts are based on the rich local oral tradition of Delhi and can help us understand the cultural ethos of the time. This article presents a micro-history of an urban structure, showing how local narratives of sacredness were shared and how new contexts were provided for architecture to create the sacred Islamic geographies of the Indian Subcontinent.